A higher ratio of IL-2/IL-4 may be an early predictor of acute graft-versus-host disease after allogeneic hematopoietic stem cell transplantation - Yu Fu; Meifang Zhao; Xiaoliang Liu; Sujun Gao; Yehui Tan (Frontiers in Immunology)
ObjectivesTo investigate the correlation between cytokines at different time points after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and the onset, severity, and therapeutic efficacy of acute graft-versus-host disease (aGVHD).MethodsWe performed a retrospective analysis of patients who underwent allo-HSCT from January 2019 to December 2021. Patients were divided into a training (first two years) and validation cohort (third year). Serum cytokines levels (TNF-α, IL-2, IL-4, IL-6, IL-10) on days +7, +14, +21, and +28 were measured and compared between patients developed aGVHD and those did not. Clinical characteristics were analyzed. Training cohort results were verified in the validation cohort to identify potential predictive markers for aGVHD.ResultsThe training cohort included 89 patients who underwent allo-HSCT, in which 29 patients developed aGVHD. Forty patients were enrolled in the validation cohort and 17 patients suffered aGVHD. Significant differences were observed in the doses of infused CD34+ and mononuclear cells between the two cohorts, whereas other baseline clinical characteristics were comparable. In the training set, the ratio of IL-2/IL-4 ≥1.103 on day +7 associated with an 8.87-fold increased risk of aGVHD. After excluding sepsis and engraftment syndrome cases, the IL-2/IL-4 ratio on day +7 remained associated with aGVHD. Under these conditions, IL-2/IL-4 ≥0.989 on day +7 suggested a 5.875-fold increased aGVHD risk. The validation set confirmed IL-2/IL-4 as an early and reliable aGVHD indicator. Among the 29 patients with aGVHD in the training set, 17 had grade I and 12 had grade II–IV aGVHD. TNF-α (day +7) and IL-2 (day +28) significantly increased in grade I aGVHD. After excluding sepsis and ES cases, 19 had aGVHD (12 grade I and 7 grade II–IV aGVHD). No cytokine was significantly associated with aGVHD severity. Twenty-two of 29 patients received corticosteroids as first-line treatment; the complete remission (CR) rate was 68.2% (15/22). Subgroup analysis revealed cytokines were comparable between patients achieved CR and those did not.ConclusionsA higher IL-2/IL-4 ratio on day +7 may be an early predictive biomarker of aGVHD onset. Nevertheless, whether these five cytokines could predict aGVHD severity or therapeutic efficacy remain unclear.